Kebijakan moneter dan kebijakan fiskal: Konsep dasar perkembangan kebijakan moneter dan fiskal - Maulidya, Nadya Nur; Zibran, Rizal (Maliki Interdisciplinary Journal, 2024)
Annual economic growth is believed to be an indicator of a region’s economic activity. Even though there is a debate (Isnan Murdiansyah, 2020) between development and economic growth, it cannot be denied that economic growth still plays an economic role in this region. Maintaining economic growth in this case requires interaction between monetary and fiscal policies. However, these two directives have different authorities. Monetary policy is implemented directly by the central government, so fiscal policy has two important components, namely wealth and the center. The interaction that occurs in monetary and fiscal policy is expected to have a positive impact on economic growth. Therefore, this research finds that adequate credit provision can have a positive impact on economic growth. Apart from that, it also identifies sectors that can be targeted to increase economic credit growth, especially East Java Province, which is the subject of this research and is expected to increase. These sectors are the service sector, industrial sector, agriculture, commercial sector and construction sector.